PHYSICAL PROCESSES OF WINTER RIVER RUNOFF FORMATION AND INFLUENCE OF ICE PHENOMENA IN THE LAKE SEVAN BASIN ON IT (Proceedings of the YSU C: Geological and Geographical Sciences, 2025)
In contemporary natural-anthropogenic complex conditions, the physical processes of the formation of winter river flow in the Sevan basin are considered using ground-based data. The values of winter water flow were calculated for 12 measuring posts on rivers that have a number of observations of 50 years or more and flow into Lake Sevan. The dependencies of the winter river flow on the river slope from the most distant point and the area of their catchment areas have been identified. It has been established that the main factors influencing the increase in winter river flow in recent decades are an increase in average daily air temperature, as well as an increase in the number of winter thaws. It was found that at all hydrometric points there is a decrease in the number of days with ice phenomena. At the same time, a close connection between winter runoff and days with ice phenomena could not be established. We plan to conduct more detailed studies on this in our future work.
Keywords: rivers of the Lake Sevan basin; winter runoff; formation; physical processes; air temperatures; thaws; linear trend coefficient